A Comparison of Vegetation and Ground‐Dwelling Ants in Abandoned and Restored Gullies and Landslide Surfaces in the Western Colombian Andes. Issue 6 (25th February 2013) - Calle, Zoraida; Henao‐Gallego, Natalia; Giraldo, Carolina; Armbrecht, Inge
Abstract Landslides and gullies are two common manifestations of land degradation in the densely populated Colombian Andes. In these unstable areas, further mass movements pose a serious threat to local populations and cause off‐site environmental damage through sedimentation, pollution, and increased flooding. A novel approach for restoring severely eroded slopes combines the use of stabilization structures made with stalks of Guadua angustifolia Kunth, Poaceae (bamboo), with high‐density planting of species that exhibit quick growth and sprouting. This study compared the vegetation and ground‐dwelling ant assemblages of 10 pairs of gullies, each pair formed by one enhanced and one untreated or control gully, 6–8 years after restoration or abandonment. The restoration treatment had significant effects on the complexity of vegetation. Average values for plant species richness, basal area, stem density, foliage density index, and total vegetation volume were 11.6, 140, 30, 11.5, and 15.6 times larger, respectively, in enhanced than in control gullies. Mirroring the differences in vegetation, average ant species richness was significantly larger (13 vs. 7.6 species per gully), and a higher proportion of ant species nested within enhanced than control gullies (52.5 vs. 30%). While control gullies were dominated by generalist ants such as Ectatomma ruidum and Linepithema angulatum, enhanced gullies had more specialized ground‐dwelling species, normally associated with high plant cover and abundant leaf litter such as Octostruma balzani and Heteroponera inca. We conclude that this restoration strategy promotes a fast recovery of vegetation and the ground‐dwelling ant fauna in these tropical mountains.